XXIV Bienal de São Paulo : "Roteiros. Roteiros. Roteiros. Roteiros. Roteiros. Roteiros. Roteiros.". - XXIV Bienal de São Paulo, 1998; Adnan, Etel; Ahmad, Jalal Al-e; Anderãos, Ricardo; Bhabha, Homi; Birnbaum, Daniel; Borges, Jorge Luis, 1899-1986.; Carvajal, Rina; Coury, Ralph M.; De Baere, Bart; Derwish, Mahmoud; Didi-Huberman, Georges; et al. (Sao Paulo : Fundaçao Bienal de São Paulo, 1998)
Konaté, Abdoulaye ; Kante, Ahmed Makki ; Maiolino, Anna Maria ; Fraser, Andrea ; Melgaard, Bjarne ; Sangar, Bülent ; Breitz, Candice ; Chen, Chieh Jen ; Choi Jeong Hwa ; Christanto, Dadang ; Salcedo, Doris ; Dadi, Elizabeth ; Dadi, Ittikhar ; Männikkö, Esko ; Alvim, Fernando ; Alÿs, Francis ; Kelly, Francis Jupurrurla ; West, Franz ; Orozco, Gabriel ; General Idea ; Lowe, Geoff ; Benin ; Altindere, Halil ; d'O, Honoré ; K., Ing ; Manglano-Ovalle, Iñigo ; Cardiff, Janet ; Wall, Jeff ; Suárez, José Antonio ; Kpobly, Joseph ; Davila, Juan ; Rabah, Khalil ; Luo Brothers (Luo Wei Bing & Luo Wei Dong & Luo Wei Guo) ; MalickSidibé ; Adams, Mark ; Raetz, Markus ; O'Connell, Maurice ; Vaisman, Meyer ; Asher, Michael ; Rio Branco, Miguel ; Tomic, Milica ; Langa, Moshekwa ; Cerkez, Mutlu ; Araki, Nobuyoshi ; Cabrita Reis, Pedro ; Dijkstra, Rineke ; Hassan, Roza El ; Keita, Seydou ; Levine, Sherrie ; Cissé, Soly ; Mulcaire, Thomas ; Ennadre, Touhami ; Molfatt, Tracey ; Grippo, Victor ; Kentridge, William ; Glotman, Yehoshua
biografie
Roteiros. Roteiros. Roteiros. Roteiros. Roteiros. Roteiros. Roteiros, XXIV Bienal de São Paulo - Pavilhão Ciccillo Matarazzo Parque Ibirapuera
Portugees & Engels
boek